Identification of miRNAs with potential roles in regulation of anther development and male-sterility in 7B-1 male-sterile tomato mutant - Omidvar, Vahid; Mohorianu, Irina; Dalmay, Tamas; Fellner, Martin (BMC genomics, 2015)
BACKGROUND: The 7B-1 tomato line (Solanum lycopersicum cv. Rutgers) is a photoperiod-sensitive male-sterile mutant, with potential application in hybrid seed production. Small RNAs (sRNAs) in tomato have been mainly characterized in fruit development and ripening, but none have been studied with respect to flower development and regulation of male-sterility. Using sRNA sequencing, we identified miRNAs that are potentially involved in anther development and regulation of male-sterility in 7B-1 mutant. RESULTS: Two sRNA libraries from 7B-1 and wild type (WT) anthers were sequenced and thirty two families of known miRNAs and 23 new miRNAs were identified in both libraries. MiR390, miR166, miR159 were up-regulated and miR530, miR167, miR164, miR396, miR168, miR393, miR8006 and two new miRNAs, miR#W and miR#M were down-regulated in 7B-1 anthers. Ta-siRNAs were not differentially expressed and likely not associated with 7B-1 male-sterility. miRNA targets with potential roles in anther development were validated using 5'-RACE. QPCR analysis showed differential expression of miRNA/target pairs of interest in anthers and stem of 7B-1, suggesting that they may regulate different biological processes in these tissues. Expression level of most miRNA/target pairs showed negative correlation, except for few. In situ hybridization showed predominant expression of miR159, GAMYBL1, PMEI and cystatin in tapetum, tetrads and microspores. CONCLUSION: Overall, we identified miRNAs with potential roles in anther development and regulation of male-sterility in 7B-1. A number of new miRNAs were also identified from tomato for the first time. Our data could be used as a benchmark for future studies of the molecular mechanisms of male-sterility in other crops.
Keywords: Flowers; MicroRNAs; neplodnost rostlin; Plant Infertility; Gene Expression Profiling; mikro RNA; květy; stanovení celkové genové exprese; Solanum lycopersicum